2020
DOI: 10.1111/tct.13187
|View full text |Cite
|
Sign up to set email alerts
|

Preparing residents to deal with human trafficking

Abstract: Background: Victims of human trafficking (HT) are predisposed to numerous health concerns. Many encounter health care practitioners during captivity, but awareness and knowledge among front-line physicians is low. Limited data exist on attempts to address this within residency training programmes. Formal curriculum time in residency is limited and online modules may be a useful educational option. Methods: Residents in family medicine, emergency medicine and general paediatrics at the University of Alberta wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Ma et al found that 81% (n = 26) of surveyed medical residents believed that HT should be incorporated into residency education, though only 6% (n = 2) of respondents reported any content in this area. 23 These findings supported ACEP's recommendation that “EMS, medical schools, and emergency medicine residency curricula should include education and training in the recognition, assessment, documentation, and interventions for patients surviving human trafficking.” 7…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…Ma et al found that 81% (n = 26) of surveyed medical residents believed that HT should be incorporated into residency education, though only 6% (n = 2) of respondents reported any content in this area. 23 These findings supported ACEP's recommendation that “EMS, medical schools, and emergency medicine residency curricula should include education and training in the recognition, assessment, documentation, and interventions for patients surviving human trafficking.” 7…”
Section: Resultsmentioning
confidence: 73%
“…Ma et al found that 81% (n = 26) of surveyed medical residents believed that HT should be incorporated into residency education, though only 6% (n = 2) of respondents reported any content in this area. 23 These findings supported ACEP's recommendation that "EMS, med-…”
Section: Roles Of Different Ed Staff In Addressing Human Traffickingmentioning
confidence: 65%
See 2 more Smart Citations